2003
DOI: 10.1038/nn1032
|View full text |Cite
|
Sign up to set email alerts
|

Processing of low-probability sounds by cortical neurons

Abstract: The ability to detect rare auditory events can be critical for survival. We report here that neurons in cat primary auditory cortex (A1) responded more strongly to a rarely presented sound than to the same sound when it was common. For the rare stimuli, we used both frequency and amplitude deviants. Moreover, some A1 neurons showed hyperacuity for frequency deviants--a frequency resolution one order of magnitude better than receptive field widths in A1. In contrast, auditory thalamic neurons were insensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

90
1,114
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 935 publications
(1,250 citation statements)
references
References 39 publications
90
1,114
11
Order By: Relevance
“…Two major types of adaptations have been described in the literature: one is the non-specific adaptation that depends on the activation history of the neuron more than on specific features of the stimulus (Calford and Semple 1995;Brosch and Schreiner 1997;McAlpine et al 2000;Ingham and McAlpine 2004;Furukawa et al 2005;Wehr and Zador 2005;Gutfreund and Knudsen 2006); the other, a higher level adaptation, is stimulus-specific adaptation (SSA), an adaptation to the history of the stimulus rather than to the activity of the neuron (Ulanovsky et al 2003(Ulanovsky et al , 2004. To distinguish SSA from non-specific adaptation, several stimulation paradigms have been used (Fig.…”
Section: Stimulus-specific Adaptationmentioning
confidence: 99%
See 3 more Smart Citations
“…Two major types of adaptations have been described in the literature: one is the non-specific adaptation that depends on the activation history of the neuron more than on specific features of the stimulus (Calford and Semple 1995;Brosch and Schreiner 1997;McAlpine et al 2000;Ingham and McAlpine 2004;Furukawa et al 2005;Wehr and Zador 2005;Gutfreund and Knudsen 2006); the other, a higher level adaptation, is stimulus-specific adaptation (SSA), an adaptation to the history of the stimulus rather than to the activity of the neuron (Ulanovsky et al 2003(Ulanovsky et al , 2004. To distinguish SSA from non-specific adaptation, several stimulation paradigms have been used (Fig.…”
Section: Stimulus-specific Adaptationmentioning
confidence: 99%
“…1). Therefore, this phenomenon has been suggested as a single-unit neural correlate of the detection of unexpected stimuli (i.e., change detection, sometimes known as novelty detection; Ulanovsky et al 2003;Perez-Gonzalez et al 2005;Malmierca et al 2009). …”
Section: Stimulus-specific Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…Neural responses to frequency (Ulanovsky et al 2003), intensity (Dean et al 2005), or ITD (Malone et al 2002;Furukawa et al 2005) have all been shown to depend on stimulus history. Recently, this has been termed "adaptive coding"; adaptive coding designates any type of change in the neural activity (not only a reduction in firing rate) that results in a more efficient encoding of the stimuli (e.g., see Dean et al 2005 for evidence of adaptive coding of intensity in the auditory modality and Fairhall et al 2001 for adaptive coding in the visual modality).…”
Section: Introductionmentioning
confidence: 99%